Double Trouble Unmasked: Femoral Pseudoaneurysm and Deep Venous Thromboses Following Coronary Angiography - Jamil, Mariam; Arshad, Khurram; Egbe, Antoine; Alamro, Yazan; Kadiri, Essa; Qaiser, Shafiq (Cardiology and Cardiovascular Medicine, 2024)
Iatrogenic pseudoaneurysms, while infrequent, represent a formidable complication of interventional cardiac catheterization, particularly in cases involving femoral artery access. This report details a unique case involving a 73-year-old male, receiving warfarin for a mechanical aortic valve, who developed a substantial right groin hematoma attributed to an iatrogenic pseudoaneurysm post-cardiac catheterization, subsequently resulting in concomitant deep venous thromboses (DVTs) in the right leg. The pathophysiology of DVTs following left heart catheterization typically involves the formation of a sizable pseudoaneurysm, exerting pressure on adjacent veins, leading to blood pooling and subsequent clot formation. Alternatively, the development of large hematomas in the thigh region may cause compression of adjacent veins. This case posed a clinical dilemma, necessitating a meticulous assessment of the risk-benefit profile associated with reversing the patient’s anticoagulation. The patient, managed with warfarin for a mechanical aortic valve, presented with deep venous thrombosis alongside a suspected actively extravasating pseudoaneurysm resulting in a groin hematoma. A secondary challenge involved determining the optimal approach for managing the pseudoaneurysm, requiring collaboration with a multidisciplinary team comprising vascular surgery, cardiology, and interventional radiology. In conclusion, despite the infrequent occurrence of major complications following left heart catheterizations, their potential life or limb-threatening nature, coupled with the rising volume of cardiac catheterizations, underscores the critical importance of early recognition of potential complications. Vigilance regarding secondary complications, such as the concurrent deep venous thromboses presented in our case, is imperative for comprehensive patient care. This case adds to the growing body of knowledge guiding clinical practitioners in managing intricate scenarios associated with interventional cardiac procedures.